Researchers' perspectives on return of individual genetics results to research participants: a qualitative study. (1st January 2021) - Mwaka, Erisa Sabakaki; Sebatta, Deborah Ekusai; Ochieng, Joseph; Munabi, Ian Guyton; Bagenda, Godfrey; Ainembabazi, Deborah; Kaawa-Mafigiri, David
ABSTRACT : Genetic results are usually not returned to research participants in Uganda despite their increased demand. We report on researchers' perceptions and experiences of return of individual genetic research results. The study involved 15 in-depth interviews of investigators involved in genetics and/or genomic research. A thematic approach was used to interpret the results. The four themes that emerged from the data were the need for return of individual results including incidental findings, community engagement and the consenting process, implications and challenges to return of individual results. While researchers are willing to return clinically significant genetic results to research participants, they remain unsure of how this should be implemented. Suggestions to aid implementation of return of results included reconsenting of participants before receiving individual genetic results and increasing access to genetic counseling services. Community engagement to determine community perceptions and individual preferences for the return of results, and also prepare participants to safely receive results emerged as another way to support return of results. Researchers have a positive attitude toward the return of clinically significant genetic results to research participants. There is need to develop national guidance on genetic research and also build capacity for clinical genetics and genetic counseling.